Kings & Queens: 1000-1399 The Millennium Series, Book 1 - Guy, John (Ticktock Publishing Ltd, 1997)
Part of The Pitkin History of Britain series, this full-color large-format publication highlights the key points in the lives of all of Britain$1 (Bs monarchs$1 (Bfrom Alfred the Great who reigned in the 9th century to Her Majesty Queen Elizabeth II.s
Keywords: Europe; Great Britain; History